PERANCANGAN INTERIOR VOKASI TUNARUNGU INTERNASIONAL DI JAKARTA TIMUR DENGAN PENERAPAN KONSEP DESAIN DEAF SPACE - Yosua Adiputra; Rr Chandrarezky Permatasari (Universitas Mercu Buana, 2020)
Vocational education is education that directs students to develop applied expertise and skills that can adapt to certain occupations and can create jobs. Vocational education aims to prepare a skilled workforce ready for work that is expected to meet employment needs. There are still limited opportunities for deaf students to continue their higher studies, this is because in Indonesia there is not yet a special applied education for deaf study in the field of arts education.So that deaf space special vocational education must be applied based on the deaf space design principles so that interior elements can support and apply in accordance with the principle of deaf space to be easier in accessibility and disability friendly.Thus the idea that was raised in the interior design of VTI was to provide children with hearing impairment to learn well and be pleasant. The concept of